Effect of Online Vinyasa Training on Housewives’ Lower and Upper Body Endurance: A Randomized Post-Pandemic Covid-19 Trial - Singh, Vikas; Singh, Mahendra Kumar; Krishna, Nibu R.; Bhutia, Tenzing Norzom; Das, Rajdeep; Ciocan, Vasile Catalin; Rajpurohit, Ravindra Singh (Physical Education Theory and Methodology, 2023)
Study purpose. The COVID-19 pandemic has a considerable impact on social and financial factors in addition to health outcomes. There is, however, still little information available as to how Covid-19 actually impacted housewives. Consequently, this paper aims to provide a new dimension to the study of how vinyasa could support mothers’ fitness throughout the pandemic. This study sought to determine whether an online vinyasa programme for 8 weeks during Covid-19 pandemic could significantly influence housewives’ upper and lower body muscle endurance. Materials and methods. 24 housewives (between the ages of 26 and 36) from the NCR region of Delhi participated in the study. The participants were divided at random and put either into the experimental group (vinyasa) or the control group. Both upper and lower body muscular endurance was found to be the health-related variable. The longest-lasting bent knee push-ups were used to gauge upper body muscular endurance, while the longest-lasting bodyweight squat holds over a 90-degree angle were used to gauge lower body muscle endurance. Results. To analyse the findings, tests were run both prior to and following the training. A substantial difference between the experimental group and control group was found using ANCOVA to compare them to the baseline after 8 weeks. Conclusions. Thus, it was determined that the online/virtual vinyasa training programme was a successful way for housewives to increase their body muscular endurance (health-related fitness).